2012
DOI: 10.1177/0020764012443756
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric advance statements: An Indian experience

Abstract: Psychotic patients with a long-term illness, a third of them from non-urban areas, were able to write a valid PAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 8 publications
0
21
3
Order By: Relevance
“…This is in contrast to findings from another study on PAD in India, which found carers to be very supportive of PADs [16]. The role of family in PADs is a delicate one, as carers may influence preferences articulated in a PAD, or may lead to tense relations if the client and carer preferences differ.…”
Section: Discussioncontrasting
confidence: 89%
“…This is in contrast to findings from another study on PAD in India, which found carers to be very supportive of PADs [16]. The role of family in PADs is a delicate one, as carers may influence preferences articulated in a PAD, or may lead to tense relations if the client and carer preferences differ.…”
Section: Discussioncontrasting
confidence: 89%
“…1) (Weinstock et al 1984;Veliz & James, 1987;Norko et al 1990;Bean et al 1994;Grisso et al , 1997Carpenter et al 2000;Moser et al 2002Moser et al , 2005Moser et al , 2006Valletto et al 2002;Wong et al 2000Wong et al , 2005Bellhouse et al 2003;Kovnick et al 2003;Vollmann et al 2003;Cohen et al 2004;Palmer et al 2004Palmer et al , 2005Srebnik et al 2004;Cairns et al 2005;Eyler et al 2005Eyler et al , 2007Koren et al 2005;Stroup et al 2005;Candilis et al 2006Candilis et al , 2008Dunn et al 2007;Moye et al 2008;Kavanagh et al 2008;Jeste et al 2009;Owen et al 2009aOwen et al , 2011De Marco et al 2010;Capdevielle et al 2009;Linder et al 2012;Di & Cheng, 2013;Fischer et al 2013;Kumar et al 2013;Lan et al 2013;Raffard et al 2013;Skipworth et al 2013;Chiu et al 2014). A clinician with expertise in the field [G Shields (GS)] ...…”
Section: Resultsmentioning
confidence: 99%
“…Predictably, ECT use remained a contentious area-a slender majority of patients (39 v/s 30) were unwilling to consider it at all (Pathare et al, 2015). A second study evaluated 92 completed model PADs of patients at SCARF, Chennai (Kumar et al, 2013). Yet again, all patients wanted to continue treatment.…”
Section: Resultsmentioning
confidence: 99%